Pengaruh Loyalitas Merek Coffee Shop di Kota Batam - Dame Afrina Sihombing; Ellys Walvinson (Program Studi Pariwisata - Universitas Internasional Batam, 2021)
Foreign tourist visits in 2019 to Batam city reached 1,431,166 visits and an increase of 5.15 percent compared to the previous year. The existence of several influences from tourists who are happy with visiting shopping centers and relaxing at coffee shops, causing Batam City to follow this lifestyle. This research uses descriptive testing method, validity test, reliability test, t-test, and determination coefficient test with foreign tourist objects. Tests were carried out using SPSS 24. The results of this study are brand satisfaction, customer brand identification and customer satisfaction have a positive influence on brand loyalty. The limitation in this study is that some foreign tourists have difficulty answering questions so it is necessary to explain the question in question and based on the results of the test results the coefficient of determination of the intervening variable and the dependent variable has a percentage that is influenced by other variables such as brand experience, brand knowledge, and so on